Detection of and adjustment for selection bias in randomized controlled clinical trials - Kennes, Lieven Nils (Henry Stewart Talks, 2020)
Introduction to selection bias, Accrual character of clinical trials, Restricted randomization procedures, Blinding, masking of past treatment assignments, Impact of 3rd order selection bias on clinical trial results, Mathematical model to detect and adjust for 3rd order selection bias, Restricted random walk, Maximum likelihood estimators and their properties, Consistency and asymptotic normality, Likelihood ratio test